Review of Hauteas Meaning and Spirituality on Timorese - Maria Delsi Abatan; Diana Aipipidely; Indra Yohanes Kiling (Journal of Health and Behavioral Science, 2021)
Humans as spiritual beings certainly have great faith, which is higher in something that is outside of themselves. This belief is what then forms himself and his actions to always direct his life to something higher and bigger. This belief or spirit to always direct is known as spirituality. Spirituality is the individual's belief in a Supreme figure and believes in a bond with his spirit. Hauteas is one of the symbols of spirituality in the village of East T'eba, Biboki Tanpah District, North Central Timor Regency. Hauteas is one of the round-shaped wood which is planted in the ground, at the top of the wood three branches form a triangle. One branch in the middle is longer and the other two are shorter. The long branches are usually pinned to Uis Neno (God). Two short branches are usually pinned to adat and government. The people of Timor are also known as Atoni Pah Meto or as gatherers, which means they like to move from place to place due to war or the danger of disease or being spread by indigenous religions and the natural surroundings that are not friendly to humans. This paper discusses literature related to spirituality and Hauteas meaning on the Timorese people.